Factors affecting the level of integrated reporting disclosure of companies listed on the stock exchange in Vietnam - Le, Bao Quyen (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2025)
The aim of this study is to identify the factors affecting the level of integrated reporting disclosure of companies listed on the Stock Exchange in Vietnam. The study used an unweighted disclosure index based on the content of the IIRC Framework with 200 listed firms in Vietnam in 2020. Ordinary least square (OLS) regression model is used to determine the factors affecting the level of integrated reporting disclosure of listed companies. The results showed that, (1) Vietnamese listed firms disclose about 40% of the information required by the IIRC Framework, and (2) The disclosure levels are positively associated with board independence, audit quality, and firm size.